P331 A screen to identify the regulators of genome stability in the human commensal Candida albicans. (20th September 2022) - Goyal, Rohit; Jaitly, Priya; Legrand, Melanie; Chauvel, Murielle; d'Enfert, Christophe; Sanyal, Kaustuv
Abstract: Poster session 3, September 23, 2022, 12:30 PM - 1:30 PM:   Objectives: Cell division is a well-regulated process ensuring high fidelity propagation of genetic material to maintain genome stability. A plethora of proteins in distinct cellular pathways, like DNA replication, repair, and segregation contribute to a stable genome. Defects in either of these processes are sensed by cellular surveillance mechanisms ensuring faithful segregation of duplicated DNA during cell division. Failure to correct these defects leads to aneuploidy and rearrangements which may affect the cell viability. On the other hand, rearrangements in the genome are a well-known mechanism for attaining drug resistance in fungal pathogens including the human commensal Candida albicans . With a major percentage of the genome being uncharacterized in C. albicans, the regulators of genome stability are poorly studied. To gain a better understanding of the regulation of genome stability and antifungal resistance, we aimed to identify and characterize novel genome stability regulators in C. albicans using an overexpression ORFeome. Methods: We utilized an overexpression library of C. albicans genes cloned under the regulatable TET-ON promoter. Each construct was stably integrated at the RPS1 locus in a C. albicans chromosomal stability (CSA) reporter strain. 1 The CSA reporter strain contains two different fluorescent markers integrated at the same allelic locus of two homologs of chromosome 4: Chr4a and Chr4b. The resulting library was used to measure increased genome instability using flow cytometry-based analysis upon overexpression of individual ORFs. Genome instability was scored by measuring the frequency of loss of one of the fluorescent markers. The distinction between chromosomal loss events and non-chromosomal loss events was made using a third fluorescence marker present at the opposite arm of chromosome 4b. Results: Out of the 532 C. albicans ORFs screened, five genes upon overexpression exhibited an increased genome instability. Two of these genes increased genome instability primarily by chromosome loss, while the remaining three exhibit genome instability due to non-chromosomal loss events. We identified one phylogenetically restricted gene, CSA11, present only in the CTG clade species of Ascomycota, with a previously unknown function in genome stability. CSA11 is important for cell cycle progression. Overexpression of CSA11 significantly increased the rate of erroneous chromosome segregation leading to aneuploidy. Conclusion: We identified a phylogenetically restricted gene, CSA11, whose overexpression resulted in chromosome mis-segregation leading to aneuploidies. Further characterization and understanding of the regulatory mechanisms of these Candidate genes may reveal unknown pathways for maintaining genome stability and drug resistance. These genes may also serve as novel targets for developing antifungals. Source: Jaitly P, Legrand M, Das A, Patel T, Chauvel M. et al, A phylogenetically-restricted essential cell cycle progression factor in the human pathogen Candida albicans . 2021; bioRxiv: 2021.2009.2023.461448.